Liablity of The Parties of Condotel Management Contract - Adrian Adhitana Tedja; Erni Agustin (Universitas Airlangga, 2019)
The increase of economic growth in Indonesia can not ignore the increasing growth of business in property by the Indonesia people. Investors does not only focus on doing business on land and landed house, but also the emergence of apartment and condominium answers the necessity towards the scarcity of land. Various form of property investment is offered, one of which is investment in the form of condotel. Condotel or condominium hotel is a new form of business in Indonesia without any specific regulation which regulates it. First, the definition of condotel is a form of high-rise building which can be owned separately and consist of joint land, joint property, and joint parts which is functioned as a hotel. These function as a hotel that needs condotel management contract to alter a regular apartment into a condotel. Condotel management contract is an innominate contract therefore it needed a further study to analyze its clauses, such as management obligation, profit sharing, duration, and discharge of contract. The characteristics of condotel management contract includes irrevocable power of attorney and obligation of building care and maintenance as well as legal relationship between the owner of condotel unit and the third parties. Understanding the characteristics of condotel management contract will determine the person liable for damages caused. This research uses normative method of research and uses statute as well as conceptual approach.